Sobre as origens das artérias frênicas em Felix catus domesticus - Liegel, Sílvio Rodolfo; Riella, Ambires Cecílio Machado; Vernalha, Milton Miró; Benato, Maria Luiza Scucato (Acta Biológica Paranaense, 1991)
Sobre as origens das artérias frênicas em Felix catus domesticus